Toward Postcolonial Liturgical Preaching: Drawing on the Pre-Columbian Caribbean Religion of the Taínos (Homiletic, 2015)
Postcolonial criticism has made its way into the field of religion mostly in the disciplines of theology and biblical studies. Little has been done to approach liturgics and homiletics from a postcolonial perspective. Building on such initial approaches, this paper recovers the tradition of the Taíno religion—the pre-Columbian religion in the Antilles prior to colonial times—and borrows from it a worldview of “complementary dualities” and a ritual pattern that embraces both conflict and unity. Drawing on the tradition of the Taíno religion and building on the work of postcolonial theologians, this paper proposes a liturgical dynamic that moves the community from spaces of tension to experiences of connectedness in order to alleviate the segregation of colonized and colonizers.